On the Vibration of Single-Walled Carbon Nanocones: Molecular Mechanics Approach versus Molecular Dynamics Simulations - R. Ansari; A. Momen; S. Rouhi; S. Ajori (Shock and Vibration)
The vibrational behavior of single-walled carbon nanocones is studied using molecular structural method and molecular dynamics simulations. In molecular structural approach, point mass and beam elements are employed to model the carbon atoms and the connecting covalent bonds, respectively. Single-walled carbon nanocones with different apex angles are considered. Besides, the vibrational behavior of nanocones under various types of boundary conditions is studied. Predicted natural frequencies are compared with the existing results in the literature and also with the ones obtained by molecular dynamics simulations. It is found that decreasing apex angle and the length of carbon nanocone results in an increase in the natural frequency. Comparing the vibrational behavior of single-walled carbon nanocones under different boundary conditions shows that the effect of end condition on the natural frequency is more prominent for nanocones with smaller apex angles.